Challenges and applications for implementing machine learning in computer vision - Kashyap, Ramgopal, 1984-; Kumar, A. V. Senthil, 1966- (IGI global disseminator of knowledge, 2020)
"This book examines the latest advances and trends in computer vision and machine learning algorithms for various applications"--